Reliable l2–l∞ and H∞ Control for Nonlinear Singular Systems via Dynamic Output Feedback - Lin Li; Yuting Kang (Abstract and Applied Analysis)
The reliable l2–l∞ and H∞ control for a class of Lipschitz nonlinear discrete-time singular systems with time delay is investigated via dynamic feedback control. The main goal of this paper is to design a generalized nonlinear controller such that, for possible actuator failures, the closed-loop system is regular, casual, and stable with a given l2–l∞ and H∞ disturbance attenuation level being satisfied. Some sufficient conditions are obtained in terms of linear matrix inequalities (LMIs), and the controller design method is also proposed. Finally, a numerical example is included to illustrate the effectiveness of our proposed results.